Neuroprotective Therapy for Stroke and Ischemic Disease - Lapchak, Paul A.; Zhang, John H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is a critical and comprehensive look at current state-of-the-art scientific and translational research being conducted internationally, in both academia and industry; it serves to address new ways to provide effective treatment to victims of ischemic and hemorrhagic stroke and other ischemic diseases. Currently, stroke can be successfully treated through the administration of a thrombolytic, but the therapeutic window is short and many patients are not able to receive treatment. Only about 30% of patients are "cured" by available treatments. Divided into five sections, the proposed volume explores historical and novel neuroprotection mechanisms and targets, new and combination therapies, as well as clinical trial design for some of the most recent bench-side research.
Reflections on Neuroprotection Research and the Path Toward Clinical Success -- Systematic review & meta-analysis: important tools in understanding -- Neuroprotection is Technology, not Science -- History of Experimental Stroke Research -- History of Neuroprotection: Trials and Tribulations -- Targeting PSD-95 As a Novel Approach in the Treatment of Stroke -- ATP Sensitive Potassium Channels (KATP) Play a Role in Hypoxic Preconditioning against Neonatal Hypoxic-Ischemic Brain Injury -- Targeting Oxidative Stress in Stroke -- Nitrones, Old Fellows for New Therapies in Ischemic Stroke -- Neuroprotective strategies via modulation of innate immune receptors -- Harnessing the power of the human immune system via multi-omic immune profiling in stroke treatment and recovery -- Polarization of microglia/macrophages in brain ischemia: relevance for stroke therapy -- Endoplasmic Reticulum Stress: An Opportunity for Neuroprotective Strategies after Stroke -- Effects of Neuroprotectants before and after stroke: Statins and Anti-Hypertensives -- Toward Effective Combination Therapy and Pleiotropic Drugs -- TRPM7 Channels as Potential Therapeutic Targets for Stroke Cholinergic Protection in Ischemic Brain Injury -- Remote Ischemic Conditioning: A Highly Translatable Therapy for Acute Stroke -- Hypothermia for Acute Ischemic Stroke -- Modern endovascular treatment of ischemic disease -- Cerebral Microbleeds and Thrombolysis for Acute Ischemic Stroke -- Targeting pericytes and the microcirculation for ischemic stroke therapy -- Thrombolytic and Endovascular Therapies for Acute Ischemic Stroke -- Sonothrombolysis for acute ischemic stroke: a critical appraisal -- Combination Therapy with Thrombolysis -- Oxygen Carriers: Are they enough for cellular support? -- A new paradigm in protecting ischemic brain: preserving the neurovascular unit before reperfusion -- The right rodent for the job: infarct variability between strains and its impact on logistics of experimental animal studies -- Rabbit Spinal Cord Ischemia Model for the Development of Neuroprotective Treatments -- Stroke Sex Differences: from basic research to clinical trials -- Unpuzzling the co-morbid type 2 diabetes and hypertension-related cognitive dysfunction and stroke -- Sex Specific Factors in Stroke -- Current Imaging Strategies for Patient Selection in Acute Ischemic Stroke Trials.
Keywords: Medicine; Neurosciences; Cardiology; Biomedicine; Neurosciences; Cardiology